Hubungan Dukungan Keluarga dengan Efektivitas Regimen Terapeutik pada Pasien Skizofrenia di Wilayah Kerja Yayasan Rumah Ceria Repok Cianjur 2022 - Anisa Alma Frima; Ahmad Rizal (Lembaga Pengembangan Kinerja Dosen, 2023)
Introduction: Non-adherence to the Therapeutic Regimen in schizophrenic patients is one of the causes of relapse in schizophrenic patients. Adherence to therapeutic regimens can be influenced by several factors, one of which is family support. Objectives: aims to determine the relationship between family support and the effectiveness of therapeutic regimens in schizophrenia patients in the work area of Yayasan Rumah Ceria Repok Cianjur Regency in 2022. Method: This study uses quantitative with a type of cross sectional approach. Sempel collection using a total sampling technique of 30 respondents and measured by questionnaire. As well as in statistical tests using the Spearman Rank test. Result: Good family support 5 (16.7%), and moderately good family support 14 (50.0%), and poor support 10 (33.3%), and effectiveness of adherent regimen 17 (56.7%), and effectiveness of non-adherence regimen 13 (43.3%). Spearman Rank statistical test and obtained p-value = 0.000. Conclution: The relationship between family support and the effectiveness of therapeutic regimens in schizophrenia patients in the working area of Yayasan Rumah Ceria Repok Cianjur regency in 2022.